2009
DOI: 10.1038/nm.1992
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor B2 is a cellular receptor for enterovirus 71

Abstract: Enterovirus 71 (EV71) belongs to human enterovirus species A of the genus Enterovirus within the family Picornaviridae. EV71, together with coxsackievirus A16 (CVA16), are most frequently associated with hand, foot and mouth disease (HFMD). Although HFMD is considered a mild exanthematous infection, infections involving EV71, but not CVA16, can progress to severe neurological disease, including fatal encephalitis, aseptic meningitis and acute flaccid paralysis. In recent years, epidemic and sporadic outbreaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
466
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(491 citation statements)
references
References 17 publications
21
466
3
1
Order By: Relevance
“…One explanation might be that this highly passaged cloned strain of EV71 might have lost its ability to interact with HS through consecutive passages. It can also be suggested that this strain of EV71 may largely utilize one of the two recently suggested candidates for cell receptors of EV71 for fibroblasts and epithelial cell lines; SCARB2 [22], or sialic acid-linked glycans [23], independent of cell surface HS. Therefore, whilst the role of HS in interacting with this cloned strain of EV71 may not be completely overlooked, the virus adsorption is not essentially and selectively dependent on cell surface HS in Vero cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One explanation might be that this highly passaged cloned strain of EV71 might have lost its ability to interact with HS through consecutive passages. It can also be suggested that this strain of EV71 may largely utilize one of the two recently suggested candidates for cell receptors of EV71 for fibroblasts and epithelial cell lines; SCARB2 [22], or sialic acid-linked glycans [23], independent of cell surface HS. Therefore, whilst the role of HS in interacting with this cloned strain of EV71 may not be completely overlooked, the virus adsorption is not essentially and selectively dependent on cell surface HS in Vero cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that although Human Scavenger Receptor Class B, Member 2 (SCARB2) was previously demonstrated to be the dominant EV71 receptor in epithelial cell lines [22], the presence of another minor receptor(s) in one of the tested susceptible cell lines was also suggested, which could facilitate EV71 infection through a SCARB2-independent pathway [22]. This is also in agreement with a general fact that picornaviruses easily adapt to bind to different co-receptor(s) even in the same cell type due to having the flexibility in receptor usage [1,6,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining skin part; particularly buttock, perianal and other region were free of any lesion. (PSGL-1), human scavenger receptor class B, member 2 (SCARB2), and sialic-acid-linked glycanact as functional receptors for EV71 by using different human cell lines and different cloning strategies [6,7,8].…”
Section: Case Reportmentioning
confidence: 99%
“…In 2009, researchers reported the discovery of two EV71 receptors, i.e. human scavenger receptor class B, member 2 (SCARB2), also known as lysosomal integral membrane protein 2 (LIMP-2) or CD36b like-2; and P-selectin glycoprotein ligand-1 (PSGL-1), also known as CD162 [9][10][11]. SCARB2 is expressed in most cell types, whereas PSGL-1 is limited to blood cells and endothelial cells, suggesting a distinct role for these two receptors in the pathogenesis of EV71 infection in vivo [12].…”
Section: Introductionmentioning
confidence: 99%